2010
DOI: 10.1007/s10726-010-9191-9
|View full text |Cite
|
Sign up to set email alerts
|

No Show Paradox in Condorcet k-voting Procedures

Abstract: In this paper we extend the negative known results about No Show Paradox in Condorcet voting functions and correspondences to the contexts of k-functions and k-correspondences, in which the outcome of the voting process is a unique k-committee (set of k candidates) or a family of k-committees. The main result of the paper states that for every Condorcet k-function and for every Condorcet k-correspondence, there are situations in which every optimistic or pessimistic voter with some specific preferences could m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Both of these questions are addressed in our paper. Pérez, Jimeno, and García (2010) and Pérez, Jimeno, and García (2015) revisited participation for the optimist extension with varying notions of Condorcet-consistency. Pérez et al (2010) derived incompatibilities using a set-valued variant of Condorcet-consistency for irresolute SCFs that always select exactly k alternatives.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these questions are addressed in our paper. Pérez, Jimeno, and García (2010) and Pérez, Jimeno, and García (2015) revisited participation for the optimist extension with varying notions of Condorcet-consistency. Pérez et al (2010) derived incompatibilities using a set-valued variant of Condorcet-consistency for irresolute SCFs that always select exactly k alternatives.…”
Section: Related Workmentioning
confidence: 99%
“…Pérez, Jimeno, and García (2010) and Pérez, Jimeno, and García (2015) revisited participation for the optimist extension with varying notions of Condorcet-consistency. Pérez et al (2010) derived incompatibilities using a set-valued variant of Condorcet-consistency for irresolute SCFs that always select exactly k alternatives. Inspired by early work by Holzman (1988) on resolute SCFs, Pérez et al (2015) showed that participation is compatible with Condorcet-consistency if Condorcet winners need the support of a supermajority rather than a simple majority.…”
Section: Related Workmentioning
confidence: 99%
“…The motivation is different for a strategic protest vote, and the support given by abstaining is tenuously different from one of the most important monotonicity paradoxes revealed by Plassmann and Tideman (), Nurmi (), and Felsenthal () as a conditional paradox: the no‐show paradox (Fishburn and Brams ), also known as the extreme truncation paradox (see Brams ), or the abstention paradox (Pérez, Jimeno, and García ). This paradox states that the removal of a ballot or the absence of a voter might change the outcome of an election to a more preferable choice for that voter than if he or she decided to vote sincerely according to his/her preferences.…”
mentioning
confidence: 89%
“…4 Without being exhaustive, we can list Arrow and Hurwicz (1972), Packard (1979), Nitzan and Pattanaik (1984), Pattanaik and Peleg (1984), Barberà et al (1984), Pérez et al (2012).…”
Section: The Extension Rulementioning
confidence: 99%